2016
DOI: 10.4317/medoral.21074
|View full text |Cite
|
Sign up to set email alerts
|

Coronectomy of impacted mandibular third molars: A meta-analysis and systematic review of the literature

Abstract: BackgroundCoronectomy is an alternative to complete removal of an impacted mandibular third molar. Most authors have recommended coronectomy to prevent damage to the inferior alveolar nerve during surgical extraction of lower third molars. The present study offers a systematic review and metaanalysis of the coronectomy technique.Material and MethodsA systematic review and meta-analysis was performed based on a PubMed and Cochrane databases search for articles published from 2014 and involving coronectomy of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 26 publications
3
43
0
3
Order By: Relevance
“…This aspect is of great relevance for surgeons, since previous studies have reported that an intimate relationship between the tooth and the canal may influence the decision to perform an alternative procedure (i.e., a coronectomy). 16,17 Our results have verified those of earlier reports concerning the influence of voxel size on the assessment of anatomic and pathologic features of the oral and maxillofacial region (periodontal defects, root fractures, root resorptions, and erosion in the temporomandibular joint). [18][19][20][21][22] Other studies, however, have not been able to identify any relevant influence of voxel size on image assessment.…”
Section: Discussionsupporting
confidence: 89%
“…This aspect is of great relevance for surgeons, since previous studies have reported that an intimate relationship between the tooth and the canal may influence the decision to perform an alternative procedure (i.e., a coronectomy). 16,17 Our results have verified those of earlier reports concerning the influence of voxel size on the assessment of anatomic and pathologic features of the oral and maxillofacial region (periodontal defects, root fractures, root resorptions, and erosion in the temporomandibular joint). [18][19][20][21][22] Other studies, however, have not been able to identify any relevant influence of voxel size on image assessment.…”
Section: Discussionsupporting
confidence: 89%
“…In 1989, Knutsson et al first described coronectomy as a viable surgical option for lower third molars with a high risk of inferior alveolar nerve injury . It removes only the crown of a lower third molar and leaves the remaining root within the dentoalveolar bone.…”
Section: Introductionmentioning
confidence: 99%
“…In 1989, Knutsson et al first described coronectomy as a viable surgical option for lower third molars with a high risk of inferior alveolar nerve injury. [1][2][3][4] It removes only the crown of a lower third molar and leaves the remaining root within the dentoalveolar bone. This treatment option has been proven in randomized clinical trials to be effective in preventing inferior alveolar nerve injury, and is also safe in the long term with only minimal postoperative morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…-3 meta-analyses [11,12] -4 randomized controlled trials [13,14] -5 nonrandomized controlled trials [6,16] -6 prospective cohort follow-up studies [9,[17][18][19][20][21][22][23][24] -7 retrospective studies [25][26][27] -8 randomized controlled trial without statistical analysis [15].…”
Section: Literature Reviewmentioning
confidence: 99%